A study on Information needs of Academic staff members of Rajarata University of Sri Lanka (RUSL) - Illangarathne, S.K.; Dharmarathne, C.S. (Information for Social Development Abstracts ; 3rd LIS Research symposium, 2012)
Attached
Keywords: Information Needs; Information Seeking Behavior; University Academics; Rajarata University; Sri Lanka